The Tradition of Writing Qur’anic Commentaries in Java and Sund - Nurtawwab, Ervan (Lajnah Pentashihan Mushaf Al-Qur'an, 2009)
This article aims to examine the tradition of writing or copying QurÃ¢â‚¬â„¢anic commentaries in the Javanese and Sundanese cultural regions of the island of Java from 18thÃ‚Â to early 20thÃ‚Â centuries in terms of the choice of script, language and wrting styles, as well as the socio-historical background behind the production of such manuscripts. Some works are however available in printed forms. I also investigate how far these manuscripts contributed to the making of local Islam in Southeast Asia, specifically in Java and Sunda.